Identification and analysis of a novel microsatellite marker within the growth hormone gene promoter of Colossoma macropomum (Characiformes: Characidae) detected by TAIL‐PCR. (16th February 2021) - Jaser, Suhaila K. K.; Perazza, Caio A.; Fávaro, Léia C. L.; Goto, Mariana A.; de Oliveira, Alzira M.; Hallerman, Eric; Hilsdorf, Alexandre W. S.
Summary: While in all vertebrates, growth hormone (GH) promotes post‐natal growth, in fishes it also affects such metabolic functions as foraging rate, digestion, osmoregulation, and reproduction. The promoter region of the GH gene is an important target for studies of mechanisms regulating its expression, and polymorphisms within the promoter have been associated with performance traits in fishes. We used Thermal Asymmetric Interlaced PCR (TAIL‐PCR) to amplify and sequence the 5′‐flanking regions of the Colossoma macropomum GH (cmGH) gene. Based on a sequence of 1, 038 bp, we designed three specific nested primers (R‐290, R‐186 and R‐26) which were used with shorter arbitrary degenerate primers to amplify the 5′ proximal region of the cmGH gene. We identified a tetranucleotide (ATCC)4 microsatellite motif in this region, exhibiting four alleles (118, 122, 126 and 130 bp) within the population study. Genotypes at this locus deviated significantly from Hardy–Weinberg expectations ( p ≤ .05) and showed a low level of polymorphism (polymorphic information content = 0.163). High homozygosity ( F IS = 0.147) was observed in the overall population. The polymorphism at the microsatellite makes it an important candidate for association studies between the respective genotypes, growth rate and other traits in farmed populations. Such studies may contribute to future breeding programs using marker‐assisted selection upon this aquaculturally important species.